Attentional Patterns Toward Pain-Related Information: Comparison Between Chronic Pain Patients and Non-pain Control Group - Lee, Jieun; Ahn, Suk-Won; Wachholtz, Amy; Lee, Jang-Han (Frontiers in Psychology, 2020)
The present study compared attentional patterns to pain-related information between chronic pain patients and non-pain control group and examined similarity and difference between those two groups in their attentional patterns to pain-related information. We also investigated how pain catastrophizing and other psychological factors in chronic pain patients affected attentional patterns to pain-related information. Forty chronic pain patients from the department of neurology and rheumatology of a University Hospital and 40 participants without chronic pain from a University that is located in Seoul, Korea were recruited for the present study. Patients observed pictures of faces displaying pain, presented simultaneously with neutral expressions, while their eye movements were measured using the eye-tracking system. Independent t-tests were conducted to investigate attentional preference to pain stimuli for chronic pain and control group. No significant differences in pain-neutral pairs were found for both chronic pain and control group. A one-way MANOVA was conducted to examine the role of pain catastrophizing on psychological factors and attentional engagement to pain stimuli. No significant results for the attentional bias to pain stimuli among chronic pain patients may indicate that chronic pain patients who have suffered from chronic pain for a long time and have been treated for their chronic pain in the hospital may interpret pain-related information not as threatening. Clinical implications related to use in pain treatment and future research suggestions are discussed.